Recombinant HBV vaccine enhances the rate of sustained virological response when early initiated after anti‐HCV combination therapy. Issue 1 (17th July 2015) - Hanafy, Amr Shaaban; Farag, Alaa Ahmad; Hassanin, Hassan Mahmoud; Hassaneen, Ahmad Mahmoud
Abstract : The overall SVR rate for chronic hepatitis C genotype 4 using the Standard of care is 54.3%. HBV infection can be prevented by the administration of effective and safe vaccine. Evaluation of the vaccination‐induced anti‐HBs response rates in a cohort of HCV Egyptian patients after being exposed to antiviral combination therapy and the magnitude of its effect on the rate of SVR through its putative role in induction of crossed immunity. (A) 500 HCV patients who had completed the course of antiviral therapy and achieved ETR were retrospectively analyzed and received 20 μg of recombinant DNA vaccine for hepatitis B at time intervals (0, 1, and 4 months). The first dose of the vaccine was initiated one month post treatment. (B) Laboratory analysis: Included routine preliminary investigations to anti viral therapy and specific investigations as determination of anti‐HBs antibodies 2 months following the third dose of vaccine. 433 patients showed protective response (86.6%), 67 patients were non‐responders (13.4%) ( P  = 0.003). Adding HBV vaccine 1 month post‐treatment increased SVR (400 patients, 80%) (χ 2  = 40.3, P  = 0.000). Diabetes affect response to HBV vaccine ( P  = 0.0001). Adding HBV vaccine to the post treatment care of patients with HCV after termination of antiviral therapy gain two benefits; protection from HBV and significant increase in rates of SVR. J. Med. Virol. 88:86–93, 2016 . © 2015 Wiley Periodicals, Inc.